SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN HAMA PENYAKIT TANAMAN JAGUNG MENGUNAKAN SIMPLE ADDITIVE WEIGHTING - Suprapti Suprapti; Siti Mukodimah; Erma Dwiyani (LPPM STMIK Pringsewu, 2019)
The development of globalization that agricultural diindonesia still many problems to be overcome .To help in determining pest disease , it takes the support system decision .A method of simple additive weighting used to scrutinize pest plant disease corn .This method chosen because it is able to select alternative best of a number of the alternatives .A function of this method that is determine the value of weights to each alternative and kriteria-kriteria the judgment that has been determined .There are seven the criteria used in this research viz: caterpillar leaves, flies seeds, caterpillar agrotis, bulai, blight leaves or the rust leaves, caterpillar tongkol, new leaves and new stems.Of the study were obtained three scores alternative highest namely v1 with the 0,64, v2 with the 0.76 and v5 with the 0,96 and three the alternative elected as an alternative worst expressed meet the criteria pest plant disease corn.